MY SAY: Making work experience and training count - Abd Razak, Dzulkifli (2011)
The UK's Shadow Secretary of State for Education Andy Burnham recently made a suggestion that could be beneficial to us as we reconstruct our vocational and technical education system. Burnham suggested that work experience placements or training should be advertised to give everyone a chance to try out for them, especially those with poor and disadvantaged backgrounds and are most likely to miss out if offers are confined to "conversations around the dinner table" or arranged through connections. As jobs become scarce, work experience and on-the-job training have become the "new" criteria for employers seeking suitable candidates. These are informal and unofficial requirements but have created a Catch-22 situation for many.